New framework for the development of clinical guidelines in Russia - D. V. Blinov; E. S. Akarachkova; A. S. Orlova; E. V. Kryukov; D. I. Korabelnikov (Фармакоэкономика)
Aim - based on the existing regulations and recent documents from the regulatory bodies, determine the methodology for the development of clinical guidelines (CG) that meet the requirements of the legislation in the Russian Federation.Materials and methods. We analyzed a number of regulatory and subordinate acts confirming the concept and status of the CG, in particular, the Federal Law № 323-ФЗ “On the principles of health care for citizens of the Russian Federation”, Federal Law № 489-ФЗ “On the amendments to article 40 of the Federal Law “On compulsory medical insurance in the Russian Federation” and the Federal Law “On the principles of health care for citizens of the Russian Federation” concerning clinical guidelines, Order № 102н of the Ministry of Health of the Russian Federation dated 28 Feb 2019 “Regulations on the scientific and practical council of the Ministry of Health of Russia” and Order № 103н of the Ministry of Health of the Russian Federation of 28 Feb 2019 “On Approval of the procedure and terms for the development of clinical guidelines and their revision, the model format of clinical guidelines and requirements to their structure, contents and scientific validity of the information included in the clinical guidelines”. In addition, we used the documents of regulatory bodies of the Russian Federation, expert opinions from medical professionals and non-profit organizations as well as leading opinions from public sources.Results. Order № 102н of the Ministry of Health of the Russian Federation secured the right of the scientific and practical council to consider and decide on the CG. Order № 103н of the Ministry of Health of the Russian Federation approved the procedure and deadlines for the development/revision of the CG; the typical format of CG; the requirements for the structure of CG, its contents and scientific validity of the information included in the CG. A step-by-step algorithm was created for the procedure and timing of CG development and update; the above documents elaborate on the requirements to the structure of CG, the contents and scientific validity of the information included. There are also comments on the development and design of each CG section (title page, table of contents, list of abbreviations, terms and definitions, brief information on the disease, diagnosis, treatment, medical rehabilitation, prevention and follow-up care, organization of medical care, additional information, criteria for assessing the quality of medical care, list of references, composition of the working group on the development and revision of the CG, methodology of the development of the CG, reference materials, algorithms for doctor’s actions, patient information, assessment scales, questionnaires, and other patient assessment tools). The recently adopted requirements for CG registration are compared with the previous methodological recommendations of the regulatory bodies.Discussion. The unification of treatment strategies and the use of evidence-based reasoning in the updated CG will improve the quality of medical care and have a positive impact on the medical insurance segment and the judicial decisions. However, the presented concept of CG has attracted a number of critical comments from representatives of the medical community and medical lawyers. For example, the updated regulatory acts do not specify the deadlines and algorithms for updating the CG; these acts do not address the coordination between various medical non-profit organizations although such coordination is needed to avoid work duplication; the acts determine no specific resources required for the CG development (the latter flaw may have a negative impact on the quality and timing of the resulting CG). Some experts believe that it would be advisable to implement the system called GRADE. In addition, possible legal risks are analyzed in light of the fact that the CG are not regulatory legal documents.Conclusion. Periodic improvements in the CG renewing and approving procedure are an integral part of this large-scale process that introduces changes in the regulatory framework and clinical practice. Compulsory adherence to the CG is a due element of today’s high quality medical care.